The influence of unrelated diversification and ownership structure on firm value: Evidence from Philippine conglomerates - Pratyaksa, Rorian (Animo Repository, 2015)
Recent trends show that top Philippine conglomerates, with more than 91% of the Philippine Stock Exchange Index (PSEi) market capitalization, have continued to diversify into non-core industries (Santiago & Magpayo, 2007; Gutierrez & Rodriguez, 2013). We examine the effect of diversification on firm excess value, with considerations of ownership structure, particularly the supermajority status and family ownership while controlling for firm characteristics and industry sectors for 167 PSE-traded firms from 2004 to 2013. Results suggest that existence of a discount effect, where there is a 43% to 56% discount when diversifying into another industry. However, this discount can be offset by ownership structure characteristics, wherein having a supermajority status enjoys a 33% premium and being family-owned enjoys a 25% to 54% premium. We find that conglomerates can extract benefits from diversification strategies through the composition of their ownership structure. © 2015 by De La Salle University.